Flexible pillar-base structured piezocomposite with aligned porosity for piezoelectric energy harvesting. (October 2021) - Yan, Mingyang; Zhong, Junwen; Liu, Shengwen; Xiao, Zhida; Yuan, Xi; Zhai, Di; Zhou, Kechao; Li, Zhaoyang; Zhang, Dou; Bowen, Chris; Zhang, Yan
Abstract: Flexible piezoelectric energy harvesters have attracted significant attention in recent years due to their ability to convert strain energy associated with bending into electrical energy for low-power wearable electronic devices. Compared with 0–3 type piezoelectric composites, where the piezoelectric phase is isolated within the material, flexible piezoelectric energy harvesters based on a three-dimensional interconnected ceramic skeleton are of particular interest due to their high stress transfer capability and high piezoelectric coefficients. Herein, a three-dimensional interconnected porous barium calcium zirconate titanate (BCZT) pillar-based structure is created via freeze casting, where polydimethylsiloxane (PDMS) is impregnated into the aligned pore channels to form a flexible piezoelectric energy harvester. The effect of porosity on piezoelectric coefficients, ferroelectric properties and energy harvesting performance is investigated in detail. The piezoelectric coefficient and energy harvesting figure of merit are significantly enhanced due to the presence of an aligned pore structure which leads to a high transfer of applied stress into the piezoelectric phase. The highly aligned porosity leads to the creation of a piezoelectric composite with 60 vol% of polymer that exhibits a high output voltage of 30.2 V and current of 13.8 μA. Moreover, the peak power density can reach up to 96.2 μW cm −2, which is significantly higher than that of nanoparticle-based piezoelectric composites. This work demonstrates a promising prospect of utilizing flexible piezoelectric composites for energy harvesting applications. Graphical Abstract: A flexible piezoelectric energy harvester based on BCZT pillar-base composite with aligned porosity is achieved via a freeze casting technique. Enhanced piezoelectric properties and energy harvesting performance ( V = 30.2 V, I = 13.8 μA at a porosity of 60 vol%) are realized due to the high poling efficiency and improved stress transfer, which is capable of charging capacitors and illuminating commercial LEDs. ga1 Highlights: Flexible pillar-base structured piezocomposite with highly aligned porosity is developed via freeze casting. The piezoelectric energy harvesting performance is significantly enhanced due to the presence of an aligned pore structure. Piezoelectric composite with 60 vol% of polymer exhibits a maximum power density of 96.2 μWcm −2 . It is demonstrated to have the ability to charge capacitors and illuminate commercial LED bulbs.